Analisis Rasio Solvabilitas, Likuiditas, dan Rentabilitas Tahun 2021-2023 Pada PT. Perusahaan Listrik Negara (PERSERO) - Wihelmina Maryetha Yulia Jaeng; Katharina Yuneti (Jurnal Projemen UNIPA, 2024)
PT Perusahaan Listrik Negara (Persero) (PLN) is one of Indonesia's largest state-owned enterprises (SOEs) responsible for providing electrical energy to the public and industries. This study aims to analyze the financial performance of PT PLN (Persero) during the 2021-2023 period through financial ratios, including solvency, liquidity, and profitability ratios. The data used is sourced from the annual reports of PT PLN (Persero) and analyzed using a quantitative descriptive approach. The results show a positive trend in the company's financial performance. The solvency ratio, as indicated by the debt to equity ratio, decreased from 42.71% in 2021 to 39.01% in 2023, reflecting the company's efforts to reduce debt levels. Liquidity ratios, including the current ratio and cash ratio, demonstrated significant improvements, indicating the company's enhanced ability to meet its short-term obligations. Profitability ratios such as return on equity (ROE) and return on assets (ROA) also increased, reflecting the efficiency of asset management and effective investment strategies. This study concludes that PT PLN (Persero) showed improved financial performance during the study period. For better financial sustainability, it is recommended that the company prioritize the use of retained earnings and equity capital to reduce reliance on debt and optimize asset management to support financial growth.